CAR-iNKT cells targeting clonal TCRVβ chains as a precise strategy to treat T cell lymphoma - Rowan, Aileen G.; Ponnusamy, Kanagaraju; Ren, Hongwei; Taylor, Graham P.; Cook, Lucy B. M.; Karadimitris, Anastasios (Frontiers in Immunology, 2023)
Most T cell receptor (TCR)Vβ chain-expressing T cell lymphomas (TCL) including those caused by Human T cell leukaemia virus type-1 (HTLV-1) have poor prognosis. We hypothesised that chimeric antigen receptor (CAR)-mediated targeting of the clonal, lymphoma-associated TCRβ chains would comprise an effective cell therapy for TCL that would minimally impact the physiological TCR repertoire. We show that anti-TCRVβ CAR-T cells selectively kill their cognate tumour targets while leaving >90% of the physiological TCR repertoire intact. Since invariant NKT (iNKT) cell do not incite acute graft-versus-host disease and are suitable for ‘off-the-shelf’ immunotherapy, we generated anti-TCRVβ CAR-iNKT cells. CAR-iNKT cells inhibited the growth of TCL in vivo, and were also selectively active against malignant cells from Adult T cell leukaemia/lymphoma patients without activating expression of HTLV-1. Thus we provide proof-of-concept for effective and selective anti-TCRVβ CAR-T and -iNKT cell-based therapy of TCL with the latter providing the option for ‘off-the-shelf’ immunotherapy.